SIDO-CHAR SEBAGAI PEMBENAH KERACUNAN Fe PADA TANAH SAWAH - Catherin Anggi Tiara; Fitria Dita Rahmatina; Rahmatul Fajrianeldi; Lusi Maira (Jurnal Tanah dan Sumberdaya Lahan, 2019)
Solok Regency is known as a food production centre of the community of West Sumatra and has extensive volcanic paddy fields. Paddy fields have problems of one that is the toxicity of Fe at the time of the decrease in pH, thereby resulting in low available P (Phosphate) and can decrease the production of rice. This research aimed to get the right combination of siderophore-producing bacteria by growing rice husk bio-char media in overcoming toxicity of Â iron (Fe) in the land of paddy fields in Solok Regency, and to get a pure siderophore bacterial isolate without the use of the media biochar in overcoming toxicity of Fe on paddy fields. The results of this research showed that the addition of the siderophore bacteria by using rice husk biochar could reduce the toxicity of Fe as well as improving soil available P content of paddy field. The best combination was obtained for 10 ml of siderophore bacterial isolate and 25 g of rice husk biochar.